Pathology of the Gastrointestinal Tract in Patients with Primary Hyperparathyroidism - I. A. Baranova; A. V. Baranov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To present data of Russian and foreign studies on the prevalence, pathogenesis and clinical picture of gastrointestinal tract (GIT) pathology in patients with primary hyperparathyroidism (PHPT).Key point. At the beginning of the 20th century PHPT was considered a severe endocrine disease with specific bone and kidney complications, however in 1957 W.T. St Goar proposed a mnemonic triad to recognize this pathology as “diseases of stones, bones and abdominal groans”. A high frequency of gastrointestinal complaints, peptic ulcer, pancreatitis, cholelithiasis in patients with PHPT has been reported. Hyperparathyroidism has been shown to cause smooth muscle atony with specific upper and lower GI symptoms such as nausea, heartburn and constipation. The prevalence of peptic ulcer in patients with PHPT, according to studies of the 50s–60s of the last century, ranged from 10 to 25 %. However, studies linking PHPT to peptic ulcer development were performed before the advent of proton 1). On the other hand, the development of pancreatitis in PHPT is one of the most studied pathologies. In developing countries its frequency can reach 10–20 % due to the absence of routine screening for blood calcium. Some authors report the impact of elevated parathyroid hormone levels on the formation of gallbladder stones by inhibiting of gallbladder emptying, hepatic bile secretion and mobility of the sphincter Oddi, and changing of the bile composition. A number of studies have found an increased risk of developing malignant neoplasms of the intestine, especially the colon, in patients with PHPT.Conclusion. The digestive manifestations of parathyroid dysfunction in patients can often be overlooked, and serum calcium levels should be included in the routine examination in the presence of abdominal symptoms.